Factors Regulating Plasma Protein Synthesis IV. Influence of Fragments D and E on Plasma Fibrinogen Concentration - Bocci, V; Conti, T; Muscettola, M; Pacini, A; Pessina, G. P (Thrombosis and Haemostasis, 1974)
Rabbit fibrinogen digest products (FDP) have been separated by Pevikon block electrophoresis yielding fragments D, E and other unidentified FDP.The fragments were injected into rabbits. Surprisingly, as little as 4.3 mg of fragment D elicited a significant increase in plasma fibrinogen concentration 24 hr after injection. The stimulating activity of fragment D is at least 10-fold higher than that of fragment E.